Konseling Kognitif Menggunakan Teknik Biblioterapi Untuk Mengatasi Rasa Rendah Diri Pada Remaja - Siti Afifatur Rohmah; Tri Windi Oktara (Program Studi Bimbingan Konseling Islam Fakultas Dakwah Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2023)
According to experts, a key factor in giving children a strong sense of self-esteem is having unique personal qualities such as resourcefulness, intelligence, and talents that are recognized by others. One of the main factors that differentiates humans from other animals is self-confidence, or the ability to form an identity and then give it value. The problem discussed in this study is how the Cognitive Counseling Approach with Bibliotherapy Techniques can overcome low adolescent self-esteem at LKSA Yakenas Madani. Based on the analysis that has been put forward, it can be concluded that the counseling process through the Cognitive Counseling Approach with Bibliotherapy Techniques is implemented and running well. The Cognitive Counseling Approach with Bibliotherapy Techniques can turn negative thoughts into positive ones and increase low self-esteem in adolescents at LKSA Yakenas Madani.